Investment banking in 2008. (B), A brave new world - Stowell, David; Meagher, Evan ([London] : SAGE, 2016)
In recent years Lehman Brothers, one of the five largest investment banks in the United States, had grown increasingly reliant on its fixed income trading and underwriting division, which served as the primary engine for its strong profit growth. The bank had also significantly increased its leverage over the same timeframe, going from a debt-to-equity ratio of 23.7x in 2003 to 35.2x in 2007. As leverage increased, the ongoing erosion of the mortgage-backed industry began to impact Lehman significantly and its stock price plummeted. This study examines the case of the troubled organisation.
Originally Published in: Stowell, D., & Meagher, E. (2009). Investment Banking in 2008 (B): A Brave New World. 5-308-507(B). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; Lehman Brothers (1993-2008); electronic books; Investment banking -- Case studies; Global Financial Crisis, 2008-2009 -- Case studies